Yogyathwa Simple Access to Powerful Leadership - Fernando, Nixon; Fernando, Nixon (Pearson India, 2017)
This concept of Yoga or Yogyathwa has been articulated by many thinkers and spiritual teachers in Indian heritage covering a very wide spectrum of life. In other words, it is a Meta concept. This book articulates this concept very powerfully by invoking the concept of Yogyathwa as the basic unifying principle.With the focus on Yogyathwa as the core theme, and reflecting the message of India's heritage of thinking, the authors have through this book, created a forum where the integaration of Indian roots and global vision, becomes a living reality for every student"